Unexplained tales: The Little Red Riding Hood and the Strong Riding Hood - Canals-Botines, Mireia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The aim of this article is to carry out a brief but exhaustive study of Perrault’s story of Little Red Riding Hood and compare it with one of his modern rewritings, the version of Vivim del Cuentu. The aim is to find differences in the narrative structure, the text, the illustrations and the female characters. In short, to see the existing connections between the traditional tale and its current rewriting. The conclusions will indicate that the treatment of the characters has evolved notably, changing the narrative structure to adapt it to a more plural, less sexist and more inclusive education.